Mobilidade urbana: o problema do transporte público no município de Belém do Pará - MARTINS, Davi Maciel (2024)
Urban mobility is a problem in many cities worldwide. In addition, the study of the public transport system through the lens of law is a way of seeking to provide the right to the city, especially for the most vulnerable population. This analytical study employs a literature review and a case study to investigate the evolution of cities and the road transportation model in Brazilian cities, focusing on Belém do Pará. Although the city has extensive and solid legislation on the subject, it is not yet fully respected, given that Belém's Master Plan dates from 2008 and the Urban Transportation Master Plan from 2001, the year of the last in-depth research on the subject. As a direct effect of this, outdated planning and management is evident, resulting in companies being shut down due to lack of resources. Hence, there is a need to update the public transportation system in order to provide an adequate service for society and service providers.